Examining Mobile-IP performance in rapidly mobile environments: the case of a commuter train - Hernandez, E.; Helal, A. (Proceedings LCN 2001. 26th Annual IEEE Conference on Local Computer Networks, 2001)
Trains travel at speeds ranging from 0 to 80 m/s (0 to 288 km/hr). Providing in-train wireless Internet access to multimedia applications will require the use of a mobile networking protocol, such as Mobile-IP, to achieve uninterrupted connectivity. Although Mobile-IP represents a promising solution. its performance under "extreme" mobility is questionable. We simulated a train scenario and identified the limitations of the current Mobile-IP standard in terms of throughput, handoff and packet loss of a train moving tit different velocities. We investigated the performance of UDP- and TCP-sessions, and examined the effect of different base station interleaving distances on throughput and packet loss. The results presented are part of an investigative research into adaptive mobile networking protocols in rapidly mobile networks.